Analysis of The Share Price of Transportation Companies Listed on the Indonesia Stock Exchange (IDX) Before and After Covid-19 - Yuliana, Dwi Riska; Khairunnisa, Jihan Lathifah; Aslakhiyah, Rubaiatul; Novitasari, Sri (Universitas Mercu Buana, 2022)
The Covid-19 virus pandemic has had a major impact on Indonesia, including on the economy, exchange rates and stock prices. On March 2, 2020, the first Covid-19 case was announced in Indonesia by President Ir. Joko Widodo. This study aims to analyze stock prices of Transportation Sector Companies Listed on the Indonesia Stock Exchange before and after Covid-19. In this study, the data used is the average share price of 41 transportation companies listed on the Indonesia Stock Exchange 31 days before and 31 days after the announcement of the first case of Covid-19 in Indonesia. The data was processed using the Wilcoxon Test, through the use of SPSS version 25. The results of data processing showed that there was a significant difference in stock prices before and before the announcement of the first Covid-19 case. This is indicated by a significance value of 0.000 < 0.05. Where the price is lower than before the first case of Covid-19 was announce.